Peran Simulasi sebagai Strategi Pembelajaran PAI dalam Membangun Sikap Toleransi dan Kepedulian Sosial Siswa - Nadiatulkhairiyah Nadiatulkhairiyah; Adinda Deswita Putri; Gusmaneli Gusmaneli (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The simulation method is a teaching approach that uses mock situations to understand certain concepts, skills and principles. Its use aims to train skills, gain understanding, solve problems, increase learning activity, provide motivation, develop cooperation, encourage creativity, and understand and respect other people's opinions. In the context of Islamic Religious Education, the simulation method requires educators who are professional and have expertise in the material being taught. A conducive learning environment can be created when educators act as active facilitators in creating supportive interactions between students, educators and the classroom environment. Good support from educators is very important for the success of learning Islamic Religious Education.